Fluoroscopically guided laser lithotripsy versus extracorporeal shock wave lithotripsy for retained bile duct stones: a prospective randomised study. - Jakobs, R (1997)
BACKGROUND AND AIMS: To compare extracorporeal shock wave lithotripsy (ESWL) and laser induced shock wave lithotripsy (LISL) of retained bile duct stones to stone free rate, number of therapeutic sessions, and costs. PATIENTS: Thirty four patients were randomly assigned to either ESWL or LISL therapy. The main reasons for failure of standard endoscopy were due to stone impaction (n = 12), biliary stricture (n = 8), or large stone diameter (n = 14). METHODS: An extracorporeal piezoelectic lithotripter with ultrasonic guidance and a rhodamine 6G laser with an integrated stone tissue detection system were used. LISL was performed exclusively under radiological control. RESULTS: Using the initial methods complete stone fragmentation was achieved in nine of 17 patients (52.4%) of the ESWL group and in 14 of 17 patients (82.4%) in the LISL group, or combined with additional fragmentation techniques 31 of the 34 patients (91.2%) were stone free at the end of treatment. In comparison LISL tended to be more efficient in clearing the bile ducts (p = 0.07, NS). Significantly less fragmentation sessions (1.29 v 2.82; p = 0.0001) and less additional endoscopic sessions (0.65 v 1.6; p = 0.002) were necessary in the LISL group. There were no major complications in either procedure. CONCLUSIONS: Compared with ESWL, fluoroscopically guided LISL achieves stone disintegration more rapidly and with significantly less treatment sessions, which leads to a significant reduction in cost.